SPIRITUAL ECOLOGY IN PRACTICE: RELIGIOUS VALUES AND FOREST SUSTAINABILITY IN LAMPUNG, INDONESIA - Mansur Hidayat; Syarif Mahya; Bartoven Vivit Nurdin (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
Sustainability studies have been predominantly shaped by economic and institutional approaches, with limited attention to the role of religious values as a foundation for ecological practices in local communities. This gap is particularly significant in contexts where social and environmental relations are deeply embedded in spiritual and cultural belief systems. This study aims to examine how Islamic religious values are internalized and operationalized in forest management practices within the Repong Damar agroforestry system in Krui, Lampung, Indonesia. This research employs a qualitative approach, utilizing in-depth interviews, participant observation, and document analysis, which are further analyzed through thematic analysis. The findings reveal that key Islamic values tauhid (divine unity), amanah (trust), khilāfah (stewardship), mīzān (balance), and the moral framework of reward sin function not merely as normative beliefs, but as a lived ethical system that governs human environment relations. These values constitute a form of moral-ecological governance that shapes sustainable practices, including controlled resource extraction, intergenerational responsibility, and the ritualization of ecological activities. The study proposes a conceptual framework termed the Tauhidic Sustainability Paradigm, which integrates ontological, epistemological, and ethical dimensions of sustainability grounded in Islamic theology. This framework extends the scope of Islamic environmental ethics from a predominantly normative discourse to an empirically grounded understanding of lived practices, while also contributing to the broader discourse on sustainability by incorporating spiritual and culturally embedded perspectives. Sustainability is not solely a technocratic or economic project, but also a moral and spiritual endeavor. The integration of religious values and local wisdom plays a crucial role in fostering resilient, context-sensitive, and sustainable resource management systems.